Experiment to Enhance the Reporting of Drug Use by Arrestees in Cleveland, Detroit, and Houston, 1997 - Wish, Eric D. ([Verlag nicht ermittelbar], 2001)
This project involved an experiment conducted in three Drug Use Forecasting (DUF) [DRUG USE FORECASTING IN 24 CITIES IN THE UNITED STATES, 1987-1997 (ICPSR 9477)] program sites to determine whether using a more detailed informed consent procedure and/or altering the sequence of the interview and urine specimen collection could enhance the validity of arrestees' self-reports of drug use without adversely affecting study response rates. A 2x2 factorial design was used to assess the effects of the two manipulations. The first two experimental conditions involved administering either the standard DUF informed consent or an enhanced consent that told the arrestees more about the confidential nature of the research and the capabilities of urinalysis. The second two conditions involved collecting the urine specimen either before or after the interview was administered. The experiment included 2,015 adult arrestees from Cleveland, Ohio, Detroit, Michigan, and Houston, Texas, who were randomly assigned to one of the four experimental conditions. The experiment was designed so that the only variability across the interviews was the manipulation of informed consent and the sequencing of the urine specimen request. All other procedures of a standard DUF collection were followed. Data were collected in Cleveland between July 8 and August 22, 1997, in Detroit from August 4 to September 27, 1997, and in Houston from October 17 to November 1, 1997. Variables specific to this project include the experimental condition to which the respondent was assigned, follow-up questions asking whether the arrestee would have responded differently if assigned to the other conditions, and several dummy variables on length and type of drug use. Data from the DUF interview provided detailed information about each arrestee's self-reported use of 15 drugs. For each drug type, arrestees were asked whether they had ever used the drug, the age at which they first used the drug, whether they had used the drug within the past three days, how many days they had used the drug within the past month, whether they had ever needed or felt dependent on the drug, and whether they were dependent on the drug at the time of the interview. Data from the DUF interview instrument also included alcohol/drug treatment history, information about whether arrestees had ever injected drugs, and whether they were influenced by drugs when the crime that they were charged with was committed. The data also include information about whether the arrestee had been to an emergency room for drug-related incidents and whether he or she had had prior arrests in the past 12 months. Urine tests screened for the presence of ten drugs, including marijuana, opiates, cocaine, PCP, methadone, benzodiazepines (Valium), methaqualone, propoxyphene (Darvon), barbiturates, and amphetamines (positive test results for amphetamines were confirmed by gas chromatography). Demographic data include the age, race, sex, educational attainment, marital status, employment status, and living circumstances of each respondent.